2016
DOI: 10.1098/rsta.2015.0317
|View full text |Cite
|
Sign up to set email alerts
|

The Stone–Wales transformation: from fullerenes to graphite, from radiation damage to heat capacity

Abstract: One contribution of 12 to a theme issue 'Fullerenes: past, present and future, celebrating the 30th anniversary of Buckminster Fullerene' .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…The dimerization of a [60]­fullerene (C 60 ) van der Waals (vdW) dimer forming a short carbon nanotube (CNT) is probably the most frequently studied transformation in the field of carbon chemistry and has been observed under high pressure, high temperature, , metal reduction, light and electron irradiation, as well as mechanochemical conditions. Osawa and Tomanek proposed by theory the shortest possible path of this transformation from the vdW dimer OT-0 (Figure a), which is initiated by a cycloaddition/retrocycloaddition (Figure b), followed by a series of Stone–Wales rearrangements , (Figure c) to a D 5 d symmetry (5,5) CNT OT-24 . , Although the structure of the first long-lived intermediate, the [2 + 2] cycloadduct ( OT-1 ), was identified using X-ray diffraction and by high-resolution transmission electron microscopy (TEM), no other structures have been experimentally verified because of either their short lifetimes or the structural inhomogeneity and complexity of the intermediates. Typical for such fast cascade reactions are the many temporally overlapping transient intermediates, which appear and disappear stochastically during the transformation (Figure d).…”
Section: Introductionmentioning
confidence: 99%
“…The dimerization of a [60]­fullerene (C 60 ) van der Waals (vdW) dimer forming a short carbon nanotube (CNT) is probably the most frequently studied transformation in the field of carbon chemistry and has been observed under high pressure, high temperature, , metal reduction, light and electron irradiation, as well as mechanochemical conditions. Osawa and Tomanek proposed by theory the shortest possible path of this transformation from the vdW dimer OT-0 (Figure a), which is initiated by a cycloaddition/retrocycloaddition (Figure b), followed by a series of Stone–Wales rearrangements , (Figure c) to a D 5 d symmetry (5,5) CNT OT-24 . , Although the structure of the first long-lived intermediate, the [2 + 2] cycloadduct ( OT-1 ), was identified using X-ray diffraction and by high-resolution transmission electron microscopy (TEM), no other structures have been experimentally verified because of either their short lifetimes or the structural inhomogeneity and complexity of the intermediates. Typical for such fast cascade reactions are the many temporally overlapping transient intermediates, which appear and disappear stochastically during the transformation (Figure d).…”
Section: Introductionmentioning
confidence: 99%
“…The SW defects have been widely found in graphene, [41] carbon nanotubes, [42] and fullerenes. [43] Meanwhile, both SV and double vacancies are widely reported in experiments through a high-resolution transmission electron microscope (HRTEM). [44] The ISW is one forecasting defects by density functional theory calculations.…”
mentioning
confidence: 99%
“…[46] Besides, the SW rearrangement has important implications for the chemical, electrical, and mechanical properties of carbon materials. [43] On the contrary, the QV defect presents the largest formation energy of 0.40 eV prim −1 , which is attributed to the relatively unstable C4 structure in the carbon plane. The formation energies of the other defects are about 0.20 eV prim −1 .…”
mentioning
confidence: 99%
“…For a cluster consisting of 60 carbon atoms, the most appealing impression may be the discovery of buckminsterfullerene (BF) with a football-cage structure [30]. Following investigations revealed that, besides the lowest potential-energy BF, there exists a bunch of C 60 isomers, such as those introduced by the Stone-Wales (SW) rearrangement [31]. For a long time, researches [32][33][34] have been attempting to answer the very questions whether the isomers are able to survive in realistic systems at finite temperatures and what the probability relative to BF is.…”
Section: A For Isomers Of C60 Moleculementioning
confidence: 99%